Embedding research capacity strengthening in multi-country studies in low-and middle-income countries: learnings from sexual and reproductive health research - Anne M. Khisa; Hesborn Wao; Vanessa Brizuela; Rachidatou Compaoré; Adama Baguiya; Alejandra López Gómez; Mercedes Bonet; Seni Kouanda; Anna Thorson; Evelyn Gitau (Global Health Action)
Research capacity strengthening (RCS) can empower individuals, institutions, networks, or countries to define and prioritize problems systematically; develop and scientifically evaluate appropriate solutions; and reinforce or improve capacities to translate knowledge into policy and practice. However, how to embed RCS into multi-country studies focusing on sexual and reproductive health and rights (SRHR) is largely undocumented. We used findings from a qualitative study, from a review of the literature, and from a validation exercise from a panel of experts from research institutions that work on SRHR RCS. We provide a framework for embedded RCS; suggest a set of seven concrete actions that research project planners, designers, implementers, and funders can utilise to guide embedded RCS activities in low- and middle-income countries; and present a practical checklist for planning and assessing embedded RCS in research projects.